Multinational Financial Structure and Tax Competition - Matthias Wrede (Swiss Journal of Economics and Statistics, 2013)
This paper analyzes tax competition when welfare maximizing jurisdictions levy source-based corporate taxes and multinational enterprises choose tax-efficient capital-to-debt ratios. Under separate accounting, multinationals shift debt from low-tax to high-tax countries. The Nash equilibrium of the tax competition game is characterized by underprovision of publicly provided goods. Under formula apportionment, the country-specific capital-to-debt ratio of a multinational's affiliate is independent of the jurisdiction's tax rate. Public good provision is either too large or too small. However, there is clearly underprovision under formula apportionment if the debt externality is not negative.
Keywords: F23; H25; H42; H73; 330; Multinational enterprises; financial policy; corporate taxation; tax competition